Analisa Realisasi Anggaran Belanja Pada Pemerintah Kota Depok Tahun 2021 – 2022 - Mutia Shafa Sejati; Sonny Fransisco Siboro; Nanda Apriliyani; Savika Aulia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
When it comes to the management of any institution including the government, the budget and the Budget Realisation Report (BRA) are two important components. For the purpose of evaluating the government's financial performance, the published LRA can provide important information. The LRA financial statements, which show the realisation of revenues, expenditures, and financing, can be used to test the content of the document. The purpose of this study is to determine and evaluate the realisation of the Depok City Government's expenditure budget in 2021-2022. In this study, a descriptive quantitative methodology is used, using analytical methods such as expenditure variance analysis, growth, compatibility, and efficiency. The results of the analysis show that there will be a considerable increase in the expenditure growth ratio in 2022, as well as an increase in expenditure realisation and variance. The Depok City Government has managed its expenditure effectively in this regard.